Ivabradine on Aortic Stiffness in Patients With Heart Failure. Issue 4 (1st April 2015) - Nar, Gokay; Inci, Sinan; Aksan, Gokhan; Demirelli, Selami; Soylu, Korhan; Yuksel, Serkan; Gulel, Okan; Icli, Atilla
Abstract : Aim: The aim of this study was to evaluate the effect of ivabradine treatment on aortic stiffness by measuring aortic elastic parameters in patients with heart failure (HF) receiving ivabradine treatment. Materials and Methods: The study included clinical patients who were diagnosed with HF (ejection fraction, <35%), had sinus rhythm and persistent symptoms despite full medical treatment. The study group consisted of patients with a heart rate greater than 70 beats per minute and the control group consisted of patients with a heart rate less than 70 beats per minute. Echocardiographic measurements were conducted and aortic strain, aortic distensibility, and aortic stiffness index were calculated. Results: By the end of the twelfth month, a decrease was observed in the left ventricular end-diastolic and end-systolic volumes, whereas ejection fraction was increased ( P < 0.001). When aortic elastic parameters were evaluated between the 2 groups, there was no significant difference regarding aortic strain, aortic distensibility, and aortic stiffness index at the time of enrollment and during the visit at 3 months. At the twelfth month visit, aortic strain ( P < 0.001) and distensibility ( P < 0.001) were significantly increased, whereas there was a significant decrease in the aortic stiffness index ( P < 0.001). Conclusions: During the follow-up at 12 months, significant improvements were observed in the left ventricular functions and aortic elastic parameters along with decreased heart rate in patients with HF receiving ivabradine treatment. This outcome may indicate that ivabradine treatment may correct aortic stiffness and may reduce aortic stiffness after 1 year of follow-up.